Med fascination för Abisko; En studie av de lappländska motiven i Leander Engströms konst - Broomé,Astrid (2026)
This bachelor’s thesis examines five selected works of art by the Swedish painter Leander Engström (1886–1927), created between 1915 and 1919. This period is generally regarded as the most significant phase of Engström’s artistic production and was shaped by his time spent in Abisko, as well as by a romantic relationship that coincided with an especially vivid and expressive phase in his work. Engström is today primarily known for his depictions of the northern region of Lapland in Sweden. He pursued his artistic career within a historical context characterized by technological development and a strong nationalistic climate. This thesis explores how motifs from Lapland in Engström’s art can be understood in relation to the spirit of the time, as well as whether and how his works contribute to a specific representation of Northern Lapland. Furthermore, the analysis is discussed with a postcolonial theoretical perspective in order to provide a broader understanding and to further develop the results derived from the formal and contextual analysis of the selected works of art. The formal and contextual analysis has made it possible to understand how the works are composed, what they depict and how they can be related to the historical and cultural context. The study concludes that Engström’s artistic motifs were shaped by the surrounding historical and cultural context. At the same time, his role as an expressionist contributed to a dreamlike and expressive visual language, creating a balance between contextual influence and artistic style. In conclusion, it becomes evident that Engström had a strong fascination for the landscape and culture of Northern Lapland and especially Abisko.
Keywords: Leander Engström; expressionism; Övre Lappland; Abisko; samer; postkolonialt perspektiv; exotifiering